The Importance of Human Capitalization for Banking System (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Human capital is an intangible asset not listed on a company's balance sheet. Human capital is said to include qualities like an employee's experience and skills. Since all labor is not considered equal, employers can improve human capital by investing in the training, education, and benefits of their employees.